Aspen Leaves as a “Chemical Landscape” for Fungal Endophyte Diversity—Effects of Nitrogen Addition - Witzell, Johanna; Decker, Vicki Huizu Guo; Agostinelli, Marta; Romeralo, Carmen; Cleary, Michelle; Albrectsen, Benedicte Riber (Frontiers in Microbiology, 2022)
Abiotic and biotic factors may shape the mycobiome communities in plants directly but also indirectly, by modifying the quality of host plants as a substrate. We hypothesized that antifungal condensed tannins (CTs) would determine the quality of aspen (Populus tremula) leaves as a substrate for the endophytic fungi, and that by subjecting the plants to nitrogen fertilization (N) we could manipulate the concentrations of CTs (and other chemicals), thus changing the internal “chemical landscape”. We expected that this would lead to changes in the fungal community composition, in line with the predictions of heterogeneity-diversity relationship and resource availability hypotheses. To test the hypotheses, we conducted a greenhouse study where aspen plants were subjected to N treatment. The chemical status of the leaves was confirmed using GC/MS (114 metabolites), LC/MS (11 phenolics) and UV-spectrometry (CTs) and the endophytic communities were characterized using culture‐dependent sequencing to capture the fungal dynamics. We found that N treatment reduced the concentration of, and variation in CTs and other phenolics and increased the amino acids and sugars. We introduced beetle herbivores (H) as a second treatment and highlight the subsequent interactive effects among hosts, the fungal community, and herbivores. As expected, a handful of rare fungi were associated with and potentially vectored by the beetle herbivores, but no rapid changes in chemical traits were induced by H, and no strong effect of treatments on diversity of endophytes was found. Our findings indicate that in a controlled environment the externally induced changes did not strongly alter endophyte diversity in aspen leaves.